Development of reporter gene imaging techniques for long-term assessment of human circulating angiogenic cells. (18th March 2015) - Zhang, Yan; Kuraitis, Drew; Burgon, Patrick G; Crowe, Suzanne; Vulesevic, Branka; Beanlands, Rob S; deKemp, Robert A; DaSilva, Jean N; Ruel, Marc; Suuronen, Erik J
Abstract: The use of biomaterials and tracking the long-term fate of the transplanted cells is expected to help improve the clinical translation of cell therapies for cardiac regeneration. To this end, reporter gene strategies are promising for monitoring the fate of cells transplanted with or without a delivery biomaterial; however, their application with primary adult progenitor cells (such as human circulating angiogenic cells (CACs)) has not been extensively evaluated. In this study, human CACs were transduced with reporter genes via one of two lentiviral (LV) vectors: LV-GFP-iresTK or LV- Fluc -RFP-tTK. The mean transduction efficiency was 15% (LV-GFP-iresTK) and 13% (LV- Fluc -RFP-tTK) at multiplicities of infection (MOI) of 10 and 50, respectively. Western blot analysis confirmed HSV1- tk protein expression in transduced CACs. There was no significant difference in viability between the transduced CACs and the untreated controls at a MOI of 50 or below. However, a reduction was observed in cell viability of CACs transduced with LV- Fluc -RFP-tTK at an MOI of 100. Cell migration and angiogenic potential were not affected by transduction protocol. After 4 weeks, 80.3 ± 8.4% of the labeled cells continued to express the reporters and could be visualized when embedded within a collagen matrix scaffold. Therefore, quiescent human CACs can be stably transduced to express reporter genes without affecting their function. This reporter gene technique is a promising approach to be further tested for tracking transplanted CACs (±delivery matrix) non-invasively and longitudinally.